A drug–drug interaction study with letermovir and acyclovir in healthy participants. Issue 5 (11th January 2023) - Menzel, Karsten; McCrea, Jacqueline B.; Fancourt, Craig; Witter, Rose; Zhao, Tian; Stoch, S. Aubrey; Iwamoto, Marian
Abstract : Letermovir inhibits renal tubular organic anion transporter 3 (OAT3) in vitro and is predicted to inhibit OAT3 in vivo. Acyclovir, a substrate for OAT3, is likely to be coadministered with letermovir; therefore, letermovir may increase acyclovir concentrations. A drug–drug interaction study was conducted in healthy participants ( N = 16) to assess the effect of letermovir on acyclovir pharmacokinetics. On Day 1, participants received a single oral dose of 400 mg acyclovir; on Days 2–7, participants received oral doses of 480 mg letermovir once daily with a single oral dose of 400 mg acyclovir coadministered on Day 7. Coadministration with letermovir resulted in geometric mean ratios (90% confidence intervals) for acyclovir area under the concentration–time curve from administration to infinity and maximum plasma concentration of 1.02 (0.87–1.20) and 0.82 (0.71–0.93), respectively. No notable safety issues were reported. No clinically significant interaction was observed between letermovir and acyclovir in healthy participants and no dose adjustment is required for coadministration.